THE BENEFITS AND CHALLENGES OF USING CHATGPT IN ENGLISH LANGUAGE LEARNING. - Usmonova Maftuna Anvarjon kizi (International Journal of Literature and Language Studies, 2026)
The rapid evolution of artificial intelligence (AI) and Large Language Models (LLMs) has fundamentally transformed contemporary educational paradigms, specifically within the domain of English as a Foreign Language (EFL) and English as a Second Language (ESL) instruction. This scientific article investigates the empirical benefits and systemic challenges associated with integrating OpenAI's ChatGPT into the English language learning process. Utilizing a mixed-methods conceptual framework backed by recent data from international educational contexts, the study analyzes how real-time, dialogue-based interactions influence student proficiency across core linguistic competencies: writing development, grammatical accuracy, vocabulary acquisition, and interactive communication. The findings indicate that while ChatGPT provides highly personalized language support, instant corrective feedback, and adaptive learning environments that increase student motivation, it simultaneously poses critical challenges. These obstacles include an accelerated risk of over-reliance on automated tools, academic integrity compromises (such as undetected plagiarism), occasional algorithmic